2022
DOI: 10.1186/s12906-022-03502-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Sida cordifolia contain polysaccharides possessing immunomodulatory activity and rosmarinic acid compounds with antibacterial activity

Abstract: Background The overuse of antibiotics has led to increased antimicrobial resistance, but plant-derived biological response modifiers represent a potential alternative to these drugs. This investigation examined the immunomodulatory and antibacterial activities of Sida cordifolia (used in ethnomedicinal systems to treat infectious disease). Methods Successive extractions were performed from the roots of these plants in hexane, chloroform, methanol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Indeed, previous studies on the plant have shown that polyphenols, tannin and flavonoids are responsible for its antibacterial activities [ 9 ]. Several other studies have shown strong antimicrobial activities of rosmarinic acid mainly present in the F2 fraction of B. toxisperma [ 42 , 43 , 44 , 45 ]. Similarly, several studies have shown antibacterial and antioxidant activities of quercetin and its derivatives [ 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous studies on the plant have shown that polyphenols, tannin and flavonoids are responsible for its antibacterial activities [ 9 ]. Several other studies have shown strong antimicrobial activities of rosmarinic acid mainly present in the F2 fraction of B. toxisperma [ 42 , 43 , 44 , 45 ]. Similarly, several studies have shown antibacterial and antioxidant activities of quercetin and its derivatives [ 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…2022, 12, x FOR PEER REVIEW G. mellonella are superior to other invertebrate models due to their larger size facilitating experimental manipulation (e.g., drug administration) and the ability to grow at a wide range of temperatures (20-37 °C). In addition, they confer several key advantages over small animal models due to their short data generation time (24-48 h versus weeks), being relatively inexpensive, being not constrained by stringent ethical requirements, and in many cases, producing comparable data to animal studies [24][25][26]. Recently, its genome was fully sequenced, opening opportunities for genetic and epigenetic studies [27].…”
Section: Innate Immune Systemmentioning
confidence: 99%
“…A review of the G. mellonella non-vertebrate immune system components (e.g., melanisation, nodulation and encapsulation) [21,34], its use in toxicology studies [23] and an in-depth comparison to the mammalian immune system [33,35] is beyond the scope of G. mellonella are superior to other invertebrate models due to their larger size tating experimental manipulation (e.g., drug administration) and the ability to grow wide range of temperatures (20-37 °C). In addition, they confer several key advan over small animal models due to their short data generation time (24-48 h versus w being relatively inexpensive, being not constrained by stringent ethical requirement in many cases, producing comparable data to animal studies [24][25][26]. Recently, its ge was fully sequenced, opening opportunities for genetic and epigenetic studies [27].…”
Section: Galleria Mellonella Immune Systemmentioning
confidence: 99%
“…There is a substantial antibacterial activity of the phytocompounds against gram-positive bacteria (MIC values range from 0.5 to 2.0 mg/ml), in particular against methicillin-resistant Staphylococcus aureus (MRSA). Rosamarinic acid 4-O-β-d-glucoside (100 μM; 99.9%) significantly lowers the MRSA in vivo microbial load in MRSA infected Galleria larvae [40].…”
Section: Antimicrobial Activitymentioning
confidence: 99%